2005
DOI: 10.1111/j.1475-4762.2005.00609.x
|View full text |Cite
|
Sign up to set email alerts
|

Place‐based social exclusion: redlining in the Netherlands

Abstract: ‘Redlining’ is a form of place‐based exclusion. It is widely documented in the US, but not in Europe. This paper focuses on a comparative analysis of redlining practices in the two largest cities of the Netherlands: Amsterdam and Rotterdam. It shows that redlining was common practice in Rotterdam in 1999. In 2001, no signs of redlining were found in Rotterdam. However, ‘yellowlining’ (lower loan‐to‐value ratios) was still common in some parts of Rotterdam. In Amsterdam, no neighbourhoods were faced with redlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…As a consequence of this urgent need, they often choose neighborhoods which are in lesser demand, being the less attractive neighborhoods (Regioplan, 2005). If ethnic minorities do choose to buy a house instead of renting one, processes of redlining influence the housing choices of ethnic minorities (Aalbers, 2005). The Dutch Equal Treatment Commission recently concluded that several banks apply additional lending conditions in some parts of Dutch cities, making it particularly difficult for ethnic minorities to obtain a mortgage (CGB, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…As a consequence of this urgent need, they often choose neighborhoods which are in lesser demand, being the less attractive neighborhoods (Regioplan, 2005). If ethnic minorities do choose to buy a house instead of renting one, processes of redlining influence the housing choices of ethnic minorities (Aalbers, 2005). The Dutch Equal Treatment Commission recently concluded that several banks apply additional lending conditions in some parts of Dutch cities, making it particularly difficult for ethnic minorities to obtain a mortgage (CGB, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Filtering is the opposite of gentrification. Whereas a neighborhood undergoing gentrification experiences increasing status and reinvestment, filtering is associated with decreasing status and disinvestment, not uncommonly associated with redlining (Dingemans 1979;Squires 1992;Aalbers 2005Aalbers , 2006. Both processes are based on residential mobility; increasing or decreasing income or status of the "stayer" population is not gentrification or filtering.…”
Section: Gentrification Filtering and Social Polarizationmentioning
confidence: 99%
“…This paper focuses on uneven geographical conditions in the mortgage market of the Milan region, i.e., on exclusion from, or less favourable conditions for, mortgage loans, based on geographical differences. The paper follows research on the same topic in the Dutch cities of Amsterdam, Arnhem, Rotterdam, and The Hague (Aalbers 2003, 2005a, 2005b, 2007), and is part of the same research programme. The point of this research is not only to uncover the lines that banks draw between what they see as profitable and unprofitable investments, but also to establish how, where, and why these lines are drawn, and what the consequences are of drawing these lines—in this case in the metropolitan area of Milan, Italy.…”
Section: Overviewmentioning
confidence: 99%
“…In addition to these three factors, lenders also make an assessment of the broader macroeconomic and regulatory climate. Economic recessions may, for instance, lead to more caution on the lenders' side and may even increase the likeliness of redlining and yellowlining practices (see also Aalbers 2005b): “The purchase of consumption fund items [like housing] via mortgages and other forms of consumer credit is sensitive to the availability of money” (Harvey 1982:231). Capital switching from the primary to the secondary circuit of capital takes shape within these macroeconomic processes; capital switching between places can also take place in the third factor of assessing loan applications.…”
Section: Greenlining Yellowlining and Redliningmentioning
confidence: 99%